Profitability Analysis and Stakeholders Perception of Banana Value Chain in Nadia District of West Bengal - Sarkar, Barsha; Basu, Debabrata; Jana, Hiralal; Haque, Monirul (Indian Journal of Extension Education, 2022)
Banana occupies the highest rank among India’s fruit crops both in area and production. The study was conducted on four randomly selected banana marketing channels namely Habibpur to Kolkata marketing channel (Channel-I), Habibpur local marketing channel (Channel-II), Kalyani to Kolkata marketing channel (Channel-III), and Kalyani local marketing channel (Channel-IV) of Nadia District of West Bengal during 2019 to identify marketing efficiency of the channels and comparing them in respect of value chain management (VCM) abilities. The responses were collected from forty producers, sixteen commission agents, thirty wholesalers, forty-four retailers, and twenty consumers of the marketing channel through a structured interview schedule. It was observed that the marketing efficiency of the Channel-III for all of the four important banana varieties of ‘Singapuri’, ‘Champa’, ‘Martaman’ and ‘Kanthali’ were higher than the Channel-I because of its better transportation management system, storage management facilities, and value distribution index. The marketing efficiency of the local marketing channel was distinctly higher in respect of Kolkata marketing channels. Less number of the stakeholder’s intervention in the local market channels might be the determining factor for it.
Keywords: Value chain; Marketing efficiency; Marketing margin; Stakeholders; Producer’s share in; Producer’s share in consumers rupees